Improving Outcomes with Clinical Decision Support : An Implementer's Guide, Second Edition /: An Implementer's Guide, Second Edition. (2021) - Osheroff, Jerome. A; Teich, Jonathan M; Levick, Donald; Saldaña, Luis; Velasco, Ferdinand; Sittig, Dean F; Rogers, Kendall M; Jenders, Robert A
No abstract available